2020
DOI: 10.1111/bjh.16382
|View full text |Cite
|
Sign up to set email alerts
|

Novel Illumina‐based next generation sequencing approach with one‐round amplification provides early and reliable detection of BCR‐ABL1 kinase domain mutations in chronic myeloid leukemia

Abstract: The occurrence of mutations in the BCR-ABL1 kinase domain (KD) can lead to treatment resistance in chronic myeloid leukaemia patients. Nowadays, next-generation sequencing (NGS) is an alternative method for the detection of kinase domain mutations, compared to routinely used Sanger sequencing, providing a higher sensitivity of mutation detection. However, in the protocols established so far multiple rounds of amplification limit reliable mutation detection to approximately 5% variant allele frequency. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…This is also consistent with our earlier findings, where retrospectively tracked mutations from treatment failure were detected only in two of seven patients at diagnosis (VAF <3%). 29 In contrast to our present data, earlier studies analysing the CD34 + fraction in prospective CP-CML cohorts showed up to 32% mutation incidence. 16,17 In one of these, our team previously reported 8% BCR-ABL1 KD mutation incidence (four of 50 patients), detected with the GS Junior Roche NGS platform.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is also consistent with our earlier findings, where retrospectively tracked mutations from treatment failure were detected only in two of seven patients at diagnosis (VAF <3%). 29 In contrast to our present data, earlier studies analysing the CD34 + fraction in prospective CP-CML cohorts showed up to 32% mutation incidence. 16,17 In one of these, our team previously reported 8% BCR-ABL1 KD mutation incidence (four of 50 patients), detected with the GS Junior Roche NGS platform.…”
Section: Discussioncontrasting
confidence: 99%
“…In both studies, mutations could only be detected at progression in 58% (19/33) and 38% (three of eight) patients. This is also consistent with our earlier findings, where retrospectively tracked mutations from treatment failure were detected only in two of seven patients at diagnosis (VAF <3%) 29 . In contrast to our present data, earlier studies analysing the CD34 + fraction in prospective CP‐CML cohorts showed up to 32% mutation incidence 16,17 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While Sanger sequencing is the traditional method of detection, this technique lacks sensitivity for the early detection of BCR::ABL1 KDM. More recently, nextgeneration sequencing (NGS) approaches have demonstrated improved limits of detection and are becoming increasingly adopted [2][3][4]. Uncommon and novel mutations continue to be described in TKI-resistant CML and Philadelphia chromosome-positive acute lymphoblastic leukemia patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, SS has some limitations that may be addressed by next-generation sequencing (NGS) [Soverini et al, 2019]. Studies have shown that NGS has a higher sensitivity for mutation detection and can detect pathogenic variants and copy number changes in tumor cytokines [Deregowska et al, 2020;Romzova et al, 2020]. In particular, it has played an important role in detecting early-onset variants in the structural domain of kinases that are not detected by SS and in engaging in early clinical intervention to improve clinical care for patients [Kizilors et al, 2019].…”
Section: Introductionmentioning
confidence: 99%